A Systematic Review of Complementary and Alternative Veterinary Medicine in Sport and Companion Animals: Soft Tissue Mobilization - Anna Bergh; Kjell Asplund; Iréne Lund; Anna Boström; Heli Hyytiäinen (Animals, 2022)
Soft tissue mobilization is frequently used in the treatment of sport and companion animals. There is, however, uncertainty regarding the efficacy and effectiveness of these methods. Therefore, the aim of this systematic literature review was to assess the evidence for clinical effects of massage and stretching in cats, dogs, and horses. A bibliographic search, restricted to studies in cats, dogs, and horses, was performed on Web of Science Core Collection, CABI, and PubMed. Relevant articles were assessed for scientific quality, and information was extracted on study characteristics, species, type of treatment, indication, and treatment effects. Of 1189 unique publications screened, 11 were eligible for inclusion. The risk of bias was assessed as high in eight of the studies and moderate in three of the studies, two of the latter indicating a decreased heart rate after massage. There was considerable heterogeneity in reported treatment effects. Therefore, the scientific evidence is not strong enough to define the clinical efficacy and effectiveness of massage and stretching in sport and companion animals.